2015
DOI: 10.1353/nib.2015.0003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Treatment with Respect and Dignity in the Intensive Care Unit

Abstract: Despite wide recognition of the importance of treating patients with respect and dignity, little is known about what constitutes treatment in this regard. The intensive care unit (ICU) is a unique setting that can pose specific threats to treatment with respect and dignity owing to the critical state of patients, stress and anxiety amongst patients and their family members, and the highly technical nature of the environment. In attempt to understand various stakeholders' perspectives of treatment with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 15 publications
1
21
0
1
Order By: Relevance
“…In addition to its reliability, we are confident of the "ICU-RESPECT" index's face and content validity because our item development process was based on a robust, multi-method approach to defining the construct of respect in the ICU setting from the perspectives of patients, families, clinicians, and independent observers [9][10][11][12][13]. Furthermore, the concurrent validity of the scale is demonstrated by its ability to distinguish between groups, in this case, different intensive care units.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to its reliability, we are confident of the "ICU-RESPECT" index's face and content validity because our item development process was based on a robust, multi-method approach to defining the construct of respect in the ICU setting from the perspectives of patients, families, clinicians, and independent observers [9][10][11][12][13]. Furthermore, the concurrent validity of the scale is demonstrated by its ability to distinguish between groups, in this case, different intensive care units.…”
Section: Discussionmentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT 9 We were not surprised that the "ICU-RESPECT" index performed differently in different types of ICUs, although we did not know which direction such differences might take. We observed that surgical units scored significantly lower than the medical or disease-specific units.…”
Section: Accepted Manuscriptmentioning
confidence: 91%
See 2 more Smart Citations
“…The ICU is a singular environment which poses a specific threat to respect and dignity due to the critical conditions of the patients and the stress and the anxiety of family members, together with the highlytechnical nature of the environment [16,17]. End of life care in the ICU implies the absence of pain, the ensuring of comfort, the participation of family members, the existence of a clear prognosis and the preservation of dignity [18].…”
Section: Introductionmentioning
confidence: 99%